Ukraine, the Middle East, and the West - Prymak, Thomas M. (McGill-Queen's University Press, 2021)
"For decades, Ukrainian contacts with the outside world were minimal, impeded by politics, ideology, and geography. But prior to the Soviet period the country enjoyed diverse exchanges with, on the one hand, its Islamic neighbours, the Crimean Khanate and the Ottoman Empire, and, on the other, its central and western European neighbours, especially Poland and France. Thomas Prymak addresses geographical knowledge, international travel, political conflicts, historical relations with religiously diverse neighbours, artistic developments, and literary and language contacts to smash old stereotypes about Ukrainian isolation and tell a vivid and original story. The book treats a wide range of subjects, including Ukrainian travelers in the Middle East, from pilgrims to the Holy Land to political exiles in Turkey and Iran; Tartar slave raiding in Ukraine; the poetry of Taras Shevchenko and the Russian war against Imam Shamil in the High Caucasus; Ukrainian themes and the French writers Honoré de Balzac and Prosper Mérimée; Rembrandt's mysterious painting today titled The Polish Rider; and Ilya Repin's legendary painting of the Zaporozhian Cossacks writing their satirical letter mocking the Turkish sultan. Drawing together political and cultural history, languages and etymology, and folklore and art history, Ukraine, the Middle East, and the West is an original interdisciplinary study that reintroduces Ukraine's long-overlooked connections beyond Eastern Europe."--
Keywords: Internationella relationer; International relations in literature; International relations; International relations; Ukraina; Mellanöstern; Västerlandet; Ukraine : Relations : Middle East; Middle East : Relations : Ukraine; Ukraine : Relations : Europe, Western; Europe, Western : Relations : Ukraine; Middle East; Ukraine; Western Europe